LB749. High HBsAb Seroprotection Achieved 4 Weeks after 3 doses of HepB-CpG Vaccine in People Living with HIV (PLWH) without Prior HBV Vaccination (ACTG A5379 Group B Preliminary Results). (15th December 2022) - Marks, Kristen; Kang, Minhee; Umbleja, Triin; Avihingsanon, Anchalee; Sugandhavesa, Patcharaphan; Cox, Andrea L; Perazzo, Hugo; Price, Jennifer C; Vernon, Christina; Caruso, Stephanie; Collins, Lillian; Chiambah, Shawn; et al.
Abstract: Background: Three-dose series of conventional alum-adjuvanted Hepatitis B surface antigen (HBsAg)-based vaccines achieve seroprotection rates (SPRs) of 35-70% in PLWH. HepB-CpG, a HBsAg vaccine adjuvanted with a TLR-9 agonist, achieves high SPR in immunocompetent adults with a 2-dose regimen, but limited data exist in PLWH. Methods: A5379 is an ongoing prospective, open-label study to evaluate immunogenicity of the HBV vaccine HepB-CpG in PLWH. The HBV vaccine-naïve group consisted of PLWH without past HBV infection on antiretroviral therapy with CD4 ≥100 cells/mm 3 and HIV-1 RNA < 1000 copies/mL. Participants received 0.5 mL of HepB-CpG intramuscularly (20 mcg recombinant HBsAg and 3000 mcg of CpG 1018® adjuvant) at Wks 0, 4, and 24. Primary objectives were to determine the proportion of participants who achieve seroprotection (HBsAb≥10 mIU/mL) at Wk 28 and to assess safety. This study was designed to conclude SPR >55%, with up to 10% loss to follow-up prior to 28 wks. Results: Of the 74 eligible participants enrolled at 13 global sites: 46% were male, 66% Asian, 16% Black, 15% White and median age was 47 years (range 23-68). 27% were enrolled in the US, 65% in Thailand. Median CD4 was 625 cells/mm 3, 96% had HIV-1 RNA < 60 copies/mL, and 9% had diabetes. Primary analysis set per analysis plan consisted of 68 participants (excluded: 3 missed visit, 3 out of visit window). All 68 completed 3 doses and achieved seroprotection (100% [95% CI: 94.7%, 100%]). 88% had HBsAb >1000 mIU/mL (assay upper limit). The SPR was also 100% [CI: 94.2%, 100%] in the per protocol analysis set of 62 participants. At 8 wks after the 2nd dose, the SPR was 94.4% followed by 98.5% at Wk 24, prior to the 3 rd dose. The proportion of participants with HBsAb >1000 mIU/mL increased from 27.9% at Wk 24 to 83.8% at Wk 28. One or more AEs related to study treatment were experienced by 61% of participants (39% Grade 1, 20% Grade 2, Grade 3 malaise in one participant). Vaccination site pain (40%), malaise (26%), fatigue (23%), myalgia (22%) and headache (22%) were the most frequent AEs. Seroprotection achieved by study week. Percentage of participants achieving seroprotection over the first 28 study weeks. HepB-CpG vaccine was administered at Entry, Week 4, and Week 24. Conclusion: In this study of PLWH with no history of HBV vaccination or evidence of prior HBV exposure, 100% seroprotection was achieved at 4 weeks after 3 doses of the HepB-CpG. No unexpected safety issues were observed. Disclosures: Kristen Marks, MD, MS, Gilead Sciences: Grant/Research Support Andrea L. Cox, M.D. Ph.D., Janssen: Advisor/Consultant Jennifer C. Price, MD, PhD, AbbVie: Grant/Research Support|Gilead Sciences: Grant/Research Support|Gilead Sciences: Honoraria|Merck: Grant/Research Support|Theratechnologies: Advisor/Consultant Kelvin McKoy, M.D., M.B.A., Dynavax Technologies: Employee|Dynavax Technologies: Ownership Interest|Dynavax Technologies: Stocks/Bonds Kenneth E. Sherman, MD, PhD, AbbVie: Grant/Research Support|Gilead: Advisor/Consultant|Gilead: Grant/Research Support|Helio: Grant/Research Support|Inovio: DSMB|Intercept: Grant/Research Support|MedPace: DSMB|Theratechnologies: Advisor/Consultant|Zydus: Grant/Research Support.